Spatial yield gains in empty-row optimized rice–crab co-culture are linked to nifH-driven nitrogen compensation in border rows - Yang, Tiexin; Jin, Dandan; Dong, Liqiang; Ma, Liang; Pan, Zhengyan; Li, Zhiqiang; Sun, Fuyu; Sun, Xiaosen; Yu, Lei (Frontiers in Plant Science, 2025)
IntroductionThe rice–crab coculture system is ecologically sustainable with efficient resource utilization, but the soil nitrogen cycling mechanisms underlying yield limitations in different coculture models remain unclear. Here, we aimed to identify yield-limiting factors by comparing rice productivity between the conventional rice–crab coculture model (CK) and an optimized model (12 rows cultivated-1 row empty, ERC-12). We hypothesized that ERC-12 enhances crab activity in empty rows, thereby stimulating nifH-mediated soil nitrogen fixation to offset yield losses caused by reduced planting density.MethodsField experiments were conducted in Panjin, Liaoning Province, during 2023–2024 using two japonica cultivars, Yanjing 939 (YJ939) and Yanfeng 47 (YF47). Plots were arranged in CK and ERC-12 patterns; the latter was spatially divided into boundary (PB), intermediate (PM), and central (PC) zones. Yield components, aboveground dry matter (ADM), and nitrogen (N) accumulation were measured. Soil NH₄⁺-N, NO₃⁻-N, and other nutrients were analyzed at tillering and heading stages. Expression of nitrogen-cycling genes (nifH, nirK, nirS, etc.) was quantified by qPCR.ResultsOur results showed that although ERC-12 increased per-plant yield via marginal effects in the boundary zone (PB), total yield decreased by 4.06%-5.20% compared to CK, primarily due to yield losses in the intermediate zone (PM) and empty rows. Correlation analysis revealed that the PB zone in ERC-12 had significantly higher soil ammonium nitrogen (NH+ 4-N) content and elevated expression of the nitrogen-fixing gene nifH (p < 0.01), which promoted aboveground dry matter accumulation and yield—consistent with enhanced biological nitrogen fixation under crab activity. In contrast, the PM zone suffered from nutrient competition and reduced activity expression of key nitrogen-cycle genes such as nifH, nirK, and nirS, becoming a key yield-limiting factor.DisscussionERC-12 partially compensates for yield losses through elevating soil nifH expression, which enhances NH4 +-N supply in the PB zone. To further improve ERC-12 yield, targeted strategies should be applied to optimize rice population structure in the boundary zone, the intermediate zone, and the central zone (PC), alleviating nutrient limitations in the PM zone while maintaining the boundary yield advantage.